Information on, knowledge and utilisation of support services during pregnancy and after childbirth: cross-sectional analyses of predictors using data from the KUNO-Kids health study - Christian Apfelbacher; Susanne Brandstetter; David Rothfuß; Birgit Seelbach-Göbel; Michael Melter; Michael Kabesch (BMJ Open)
Objectives To investigate mothers’ knowledge and utilisation of antenatal and perinatal support services as well as predictors of knowledge and service utilisation.Design Cross-sectional study.Setting Prospective birth cohort in Regensburg, Eastern Bavaria, Germany.Participants 2455 mothers after delivery.Outcome measures Participants’ knowledge of distinct antenatal and perinatal support services (poor vs good, defined by median split). Participants’ use of antenatal services provided by midwife (yes, no) and of any other antenatal support services (yes, no).Results The vast majority of mothers knew at least some support services. Two-thirds of women (68.4%) reported to have used the services provided by midwives. 23.6% of women reported to have used at least one of the other antenatal services. Good knowledge of services was associated with higher education (OR 1.37, 95% CI 1.13 to 1.67), no migration background (OR 2.26, 95% CI 1.76 to 2.90), better health literacy (OR 1.04, 95% CI 1.03 to 1.06), while being primiparous (OR 0.72, 95% CI 0.60 to 0.86) and being unmarried/living with a partner (OR 0.71, 95% CI 0.57 to 0.89) reduced the chance. Predictors of service utilisation differed with regard to the services considered.Conclusions Overall, mothers had a good level of knowledge of antenatal and perinatal support services. However, we found that some groups of women were less well informed. This inequality in social predictors of knowledge of services was also partly reflected in differences in service utilisation during pregnancy.